Differences in the impact of fatherlessness based on developmental age stages: a systematic review - Siti Zuliani; Anisah Triyuliasari; Iswinarti Iswinarti (Jurnal Psikologi dan Konseling West Science, 2024)
Fatherlessness refers to the absence of a father figure during a child's developmental stages, whether physically or psychologically. This systematic review analyzes 15 international journals to explore the effects of fatherlessness across various developmental periods. The findings highlight significant consequences depending on the child's age.During childhood, the absence of a father is linked to lower academic achievement and an increased risk of engaging in delinquent behavior during adolescence and early adulthood. In adolescence, fatherlessness often contributes to identity confusion, challenges in social interactions, and uncertainty regarding sexual orientation. As individuals transition into adulthood, the absence of a father figure impacts their ability to establish healthy relationships with the opposite sex and heightens their vulnerability to psychological issues.These findings emphasize the profound influence of fatherlessness on various aspects of a child’s growth and development. The review highlights the need for continued research to delve into the nuanced effects of fatherlessness across different stages of development. Such studies are crucial for developing targeted strategies and interventions aimed at minimizing the adverse outcomes associated with the absence of a father figure. By addressing these challenges, future efforts can better support children and young adults in navigating the complexities of their developmental journey